2008
DOI: 10.1074/jbc.m706643200
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Turnover of the mTOR Complex 1 (mTORC1) Repressor REDD1 and Activation of mTORC1 Signaling following Inhibition of Protein Synthesis

Abstract: mTORC1 is a complex of proteins that includes the mammalian target of rapamycin (mTOR) and several regulatory proteins. It is activated by a variety of hormones (e.g. insulin) and nutrients (e.g. amino acids) that act to stimulate cell growth and proliferation and repressed by hormones (e.g. glucocorticoids) that act to reduce cell growth. Curiously, mTORC1 signaling is reported to be rapidly (e.g. within 1-2 h) activated by inhibitors of protein synthesis that act on either mRNA translation elongation or gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 60 publications
5
82
0
Order By: Relevance
“…Endogenous as well as exogenous REDD1 protein is rapidly degraded within less than 15 min (Fig.2 C and D) as it has also been shown by Kimball et al [29]. Katiyar et al describe ubiquitinationdependent proteasomal degradation of REDD1 [20].…”
Section: Discussionsupporting
confidence: 49%
“…Endogenous as well as exogenous REDD1 protein is rapidly degraded within less than 15 min (Fig.2 C and D) as it has also been shown by Kimball et al [29]. Katiyar et al describe ubiquitinationdependent proteasomal degradation of REDD1 [20].…”
Section: Discussionsupporting
confidence: 49%
“…In skeletal muscle, REDD1 has been shown to inhibit mTOR signaling and protein synthesis in response to dexamethasone and alcohol intoxication (67,105). In addition, Kimball et al (65) found that rapid degradation of REDD1 in muscle was associated with enhanced mTOR signaling. Recent studies in human skeletal muscle have also suggested that expression of REDD1 and REDD2 plays a role in regulating mTOR activity and protein synthesis (26,27).…”
Section: Stress Response Genes Redd1/redd2 and Mtor Signalingmentioning
confidence: 99%
“…Because of the extent to which cycloheximide augmented p70S6K phosphorylation, we examined the possibility that the mTORC1 repressor, DNA damage response 1 (REDD1) (61) was affected by the inhibition of protein synthesis as previously described (62). However, in rat hepatocytes the expression level of REDD1 was not down-regulated by cycloheximide (Fig.…”
Section: Proteomic Analysis Of Rat Livermentioning
confidence: 99%